2015
DOI: 10.2343/geochemj.2.0393
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of rare earth elements (REE) from manganese oxides to phosphates during early diagenesis in pelagic sediments inferred from REE patterns, X-ray absorption spectroscopy, and chemical leaching method

Abstract: tool to estimate sedimentary environment at the time of deposition of sediments (Chaudhuri and Cullers, 1979; Nath et al., 1997). In particular, the cerium (Ce) anomaly is a decent redox indicator of the depositional environment and has been widely employed in geochemical studies (Shimizu and Masuda, 1977; Palmer, 1985; Wang et al., 1986). To develop REE pattern as a geochemical tool for sediments or sedimentary rocks, the host phases of REEs within the sediments or sedimentary rocks should

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…Other studies have also shown that mobilization of REEs from detrital sediments, including volcanic ash, during diagenesis is common, and that authigenic Fe-Mn oxyhydroxides and authigenic phosphates are sinks of pore water REEs (Palmer and Elderfield, 1985;Elderfield and Pagett, 1986;Elderfield and Sholkovitz, 1987;Toyoda and Tokonami, 1990;Rasmussen et al, 1998;Martin and Haley, 2000;Takebe, 2005;Caetano et al, 2009;Schacht et al, 2010;Soyol-Erdene and Huh, 2013;Takahashi et al, 2015;Chen et al, 2015). Here, we extend the study of Abbott et al, (2015b) and Abbott et al (2016) to the basin scale and propose a conceptual model that relates the εNd of authigenic phases to pore water, bottom water and detrital sediment (Fig.…”
Section: A Conceptual Model Relating the εNd Of Authigenic Phase To Bsupporting
confidence: 64%
“…Other studies have also shown that mobilization of REEs from detrital sediments, including volcanic ash, during diagenesis is common, and that authigenic Fe-Mn oxyhydroxides and authigenic phosphates are sinks of pore water REEs (Palmer and Elderfield, 1985;Elderfield and Pagett, 1986;Elderfield and Sholkovitz, 1987;Toyoda and Tokonami, 1990;Rasmussen et al, 1998;Martin and Haley, 2000;Takebe, 2005;Caetano et al, 2009;Schacht et al, 2010;Soyol-Erdene and Huh, 2013;Takahashi et al, 2015;Chen et al, 2015). Here, we extend the study of Abbott et al, (2015b) and Abbott et al (2016) to the basin scale and propose a conceptual model that relates the εNd of authigenic phases to pore water, bottom water and detrital sediment (Fig.…”
Section: A Conceptual Model Relating the εNd Of Authigenic Phase To Bsupporting
confidence: 64%
“…The Ce anomaly in six Ca-rich apatite grains averaged −0.58 with a standard deviation of 0.12.This strongly-negative anomaly suggests an authigenic origin for the apatite, rather than a diagenetic one (Takahashi et al, 2015). The Ce/Ca weight ratio in the apatite standard was 0.023, and on that basis, the Ce/Ca ratio in the nodule apatite was 0.017 with a standard deviation of 0.004.…”
Section: Cerium Spot Xanesmentioning
confidence: 91%
“…A particulate phase acting as a sink when in contact with seawater will provide the best record of changes in ocean conditions through time. However, a phase that continues to act as a sink during burial will have any original seawater signature diagenetically overprinted as has already been proposed for biogenic phosphates and foraminifera (Palmer and Elderfield, 1985;Toyoda and Tokonami, 1990;Takahashi et al, 2015;Trotter et al, 2016;Zhang et al, 2016;Skinner et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…However, to date little robust, direct evidence of the role of these phases has been found. Potential host phases include Fe-Mn oxyhydroxides (e.g., Sholkovitz et al, 1994;Bayon et al, 2004;Haley et al, 2004;Ren et al, 2015;Takahashi et al, 2015), cerium oxides (e.g., Haley et al, 2004), phosphates (e.g., Kon et al, 2014;Takahashi et al, 2015;Zhang et al, 2016), biogenic silicates (e.g., Akagi et al, 2014), organic matter (e.g., Duncan and Shaw, 2003;Haley et al, 2004;Schacht et al, 2010;Kim et al, 2012;Freslon et al, 2014), volcanic ash (e.g., Vance et al, 2004;Elmore et al, 2011;Wilson et al, 2013), and clays (e.g., Cullers et al, 1975;Grandjean et al, 1987;Zhang et al, 2016). These sediment components may not contribute equally to REE cycling, and their contributions will vary in space and time as the amount of REEs remobilized from each phase is likely a function of mineralogy, mineral chemistry, reactivity, surface area, and other factors such as local pore water chemistry and redox state (e.g., Elderfield and Sholkovitz, 1987;Wilson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%